2014
DOI: 10.1037/a0035612
|View full text |Cite
|
Sign up to set email alerts
|

Child temperament and parental depression predict cortisol reactivity to stress in middle childhood.

Abstract: Children's cortisol reactivity to stress is an important mediator of depression risk, making the search for predictors of such reactivity an important goal for psychopathologists. Multiple studies have linked maternal depression and childhood behavioral inhibition (BI) independently to child cortisol reactivity, yet few have tested multivariate models of these risks. Further, paternal depression and other child temperament traits, such as positive emotionality (PE), have been largely ignored despite their pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
41
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 56 publications
8
41
0
Order By: Relevance
“…Additionally, candidate genes relevant for stress susceptibility (e.g., FKPB5, CRHR1 ) interact with ACE to predict cortisol reactivity in adolescence (42, 43). Parents’ depression and various aspects of child temperament predicted longitudinal cortisol reactivity in middle childhood (44). Cortisol reactivity exhibits moderate trait-like stability over time, and particular genetic variants for stress susceptibility, especially 5- HTTLPR and CRHR1 , predict greater cortisol stability (45).…”
Section: Biological Stress Processesmentioning
confidence: 99%
“…Additionally, candidate genes relevant for stress susceptibility (e.g., FKPB5, CRHR1 ) interact with ACE to predict cortisol reactivity in adolescence (42, 43). Parents’ depression and various aspects of child temperament predicted longitudinal cortisol reactivity in middle childhood (44). Cortisol reactivity exhibits moderate trait-like stability over time, and particular genetic variants for stress susceptibility, especially 5- HTTLPR and CRHR1 , predict greater cortisol stability (45).…”
Section: Biological Stress Processesmentioning
confidence: 99%
“…Parental as well as direct observational ratings of temperament in early childhood predict personality, behavior, and risk for psychopathology in later childhood, adolescence, and adulthood (Rothbart and Posner, 2006). In addition, temperament has been linked to differences in functioning of the HPA axis (Dougherty et al, 2013; Mackrell et al, 2014) as well as autonomic nervous system (Brooker and Buss, 2010; Huffman et al, 1998; Stifter and Fox, 1990), providing a plausible basis by which individual differences in temperament may be mechanistically linked to the gut microbiome.…”
Section: Introductionmentioning
confidence: 99%
“…Also relevant is the small literature indicating that high PE buffers the impact of other vulnerabilities to negative outcomes (Clark, 2005; Mackrell et al, 2014; Park, Belsky, Putnam, & Crnic, 1997; Tugade & Fredrickson, 2004; Wichers et al, 2007; see Davis & Suveg, 2014 for a comprehensive review). For example, Mackrell et al (2014) found that high PE in children interacted with maternal depression to predict lower cortisol stress reactivity in children, and Wichers et al (2007) found that high positive affect buffered negative affect reactivity to stress.…”
mentioning
confidence: 99%